Insights into Medicine and Surgery - Raffensperger, John G., 1928- (Cambridge Scholars Publishing, 2022)
This book explores aspects of medical history that are usually overlooked by medical historians. It begins with anthropologic literature and accounts of the early explorers which describe sophisticated medical treatments and wound care by Native Americans that were superior to European practices at the time. The book also shows that the Samhita Sushruta, an ancient Indian medical text, and one of Socrates' dialogues answer the age-old question of Hippocrates' dictum against abortion and operating for bladder stones. It then dwells at length on the University of Edinburgh, the shining center of.